CORRELATION BETWEEN TSH, T3, T4 AND HISTOLOGICAL TYPES OF THYROID CARCINOMA - Hilda Fitriyani; T. Ibnu Alferraly; Lidya Imelda Laksmi (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2018)
Thyroid carcinoma is a malignancy of the thyroid gland derived from follicular or parafollicular cells. Thyroid carcinoma is the most common endocrine gland malignancy and accounts for approximately 1% of all malignancies. Thyroid carcinoma ranked ninth of 10 most common carcinomas in Indonesia. It may occur at any age but is usually diagnosed between the 3rd and 6th decade. The incidence is three or four times higher in females than in males. Based on histological features thyroid carcinoma is classified into four major types: papillary, follicular, anaplastic and medullary carcinoma. Thyroid Stimulating Hormone (TSH), Triiodothyronine (T3), Thyroxine (T4) are thyroid gland hormones. Low T3 and T4 accompanied with high TSH levels are associated with malignancy in thyroid carcinoma. This study aimed to determine the correlation between TSH, T3, T4 hormone levels, and histological type of thyroid carcinoma at the Adam Malik Hospital Medan between 2013 and 2015. The study was a cross-sectional analytical study. The sample was be obtained using consecutive sampling method. Data were collected from medical records of thyroid carcinoma patients that had undergone pathological examination and thyroid function test at the Adam Malik Hospital Medan between 2013 and 2015. Based on the Chi-Square analysis, there was a significant difference between T3 hormone level with the histopathological type of thyroid carcinoma (p<0.001), however it did not apply to the level of T4 (p = 0.120) and TSH (p = 0.328).